The Circumstances of Carrying on Effective Health Policies in Developed Countries - Białynicki-Birula, Paweł (Journal of Public Governance, 2009)
The article concerns the circumstances of carrying on effective health policies in developed countries. Contrary to the ideas of marketiszation of medical care promoted in accordance with new public management, health care retained its specific, public character. The essential significance in this regard can be attributed to health protection which should be treated on the one hand as a fundamental goal of contemporary health systems, and on the other – as a decisive motive of state involvement in health care financing. The possibility of broadening health protection depends to a large extent on public resources, in many cases transferred by budgetary methods. Hence private voluntary health insurance may be only of a supplementary character and can not be regarded as a real alternative to public financing. When analysing health systems, a comprehensive approach is indispensable, with various aspects of health systems, not only these concerning financial sources and allocation mechanisms being taken into consideration.